Pattern and reasons for drug abuse among undergraduate students in Lagos state, Nigeria (2016)
The phenomenon of drug abuse especially among university students has globally arouse interest especially due to its implication on the mental stability of abusers. Hinged on the differential association and anomie theory, this paper focuses on the pattern and reasons for drug abuse among student in University of Lagos. Both qualitative and quantitative methods of data collection were utilized through the use of questionnaire, in-depth and key informant interviews. A sample of 200 students was selected from 4 halls of residence and off campus through the simple random technique. Quantitative data were analyzed and presented using bar charts, frequencies and percentages. Hypotheses were further tested using chi-square and T-test, while qualitative data were content analyzed. Over 70% were males, while about 80 % fall between the ages of 21-30 years. Over 80% agreed that it is wrong to take drugs without prescriptions. About a quarter of the respondents smoke cigarettes and marijuana, while over 30 percent of those who smoke do so in order to feel high and reduce stress. Aside from trying to reduce stress and feel high, smoking is done to cope and forget feelings of hurt due to betrayal. The study recommends stress reduction intervention, increased counselling and campaign against drug abuse to reduce the phenomenon in higher institutions.